Near-infrared luminous scintillator with garnet structure

By introducing chromium and antimony doped ions into scandium gallium garnet, and using improved high-temperature solid phase method to prepare scintillators, the problem of limited selection of existing materials in the near-infrared band is solved, efficient near-infrared scintillation and stability are achieved, and the radiation detection needs are met.

CN119529838APending Publication Date: 2025-02-28BEIJING UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411717261.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The choice of existing scintillator materials in the near infrared band is relatively limited, and it is difficult to meet the growing demand for radiation detection.

Method used

By introducing chromium and antimony doped ions into scandium gallium garnet, the preparation is carried out using an improved high-temperature solid phase method to build a suitable energy transfer path to achieve excellent near-infrared scintillation performance.

Benefits of technology

It achieves efficient scintillation in the near infrared region of 700-1000nm, with high environmental stability and photon yield, meeting the actual needs of radiation detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529838A_ABST
    Figure CN119529838A_ABST
Patent Text Reader

Abstract

The invention discloses a garnet-structured near-infrared luminescent scintillator, and the preparation method of the scintillator adopts an improved high-temperature solid phase method, and successfully prepares a Cr < 3 + > and Sb < 3 + > doped scandium gallium garnet scintillator through the process steps of batching, grinding, pre-sintering, high-temperature sintering, re-sintering and the like. Specifically, an oxide precursor is accurately mixed according to a stoichiometric ratio, and is sintered under a high-temperature condition (the sintering temperature is 1400-1600 DEG C). In the process, the crystal structure of the material is gradually formed, and meanwhile, doping ions are promoted to be uniformly doped into crystal lattices of the scandium gallium garnet by controlling the sintering time and temperature. In the crystal growth process, the local electronic environment in crystal lattices is optimized through selection and ion doping of A-site ions, and efficient transfer of excited state energy from a matrix to a light-emitting center is promoted. Under the processes of pre-sintering, high-temperature sintering, re-sintering and the like, doped ions in the crystal are distributed more uniformly, the formation of a non-radiative recombination center is reduced, and the luminous efficiency and the stability of the scintillator are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of scintillator radiation detection, in particular to a chromium and antimony doped scandium gallium garnet A3Sc2Ga3O 12 :Cr 3+ and A3Sc2Ga3O 12 :Sb 3+ (A=Lu, Gd, Y) near-infrared scintillator and preparation method thereof. Background Art

[0002] Scintillator materials can generate low-energy photons when bombarded by high-energy rays (such as X-rays and gamma rays), so they are widely used in medical imaging, nuclear physics, security inspection, and high-energy physics. The rapid development of high-energy particle detection and radiation imaging technology has led to an increasing demand for scintillator materials. In recent years, with the advancement of photoelectric detection technology in the near-infrared (NIR) band, scintillator materials that can emit photons in the near-infrared region have received increasing attention.

[0003] Rare earth ions have been widely reported in the field of near-infrared phosphors due to their unique electronic structure and energy level transition characteristics. Among the existing scintillator materials, the traditional rare earth ion doping system performs well in the visible light region, but the scintillator selection in the near-infrared band is relatively limited. Therefore, it is necessary to discover and develop near-infrared scintillators with low price, high stability, high brightness, and excellent radioluminescence performance to meet people's growing demand for radiation detection.

[0004] In the present invention, scandium gallium garnet (ScGaG) crystal is selected as an ideal host material due to its excellent chemical stability and mechanical properties. In addition, by selecting different A-site ions (such as Lu, Gd, Y), the density, band gap and other properties of the material can be adjusted, thereby optimizing the overall performance of the scintillator. Finally, by introducing doping ions, with the help of their luminescence characteristics, efficient scintillation luminescence can be achieved in the near-infrared band.

[0005] Chromium and antimony doped scandium gallium garnet (A3Sc2Ga3O 12 :Cr 3+ and A3Sc2Ga3O 12 :Sb 3+ ; A=Lu,Gd,Y) as a new type of near-infrared scintillator material, shows good scintillation performance, and its luminescence band covers the near-infrared region of 700-1000nm. It has high environmental stability and photon yield, providing new possibilities for scintillator energy spectrum detection and near-infrared imaging. In the future, this series of materials will have great application potential in medical imaging equipment, industrial non-destructive testing, space exploration and other fields. Summary of the invention

[0006] The present invention provides a chromium and antimony doped scandium gallium garnet A3Sc2Ga3O 12 :Cr 3+ and A3Sc2Ga3O 12 :Sb 3+ (A=Lu, Gd, Y) near-infrared scintillator and its preparation method, the method has simple process, low preparation cost and is suitable for mass production. Through ion doping, a suitable energy transfer path is built to achieve excellent near-infrared scintillation luminescence performance. There are potential applications in the fields of medical and military industry.

[0007] The preparation method of the scintillator adopts an improved high-temperature solid phase method, and successfully prepares Cr after strict process steps such as batching, grinding, pre-sintering, high-temperature sintering and re-sintering. 3+ Doping and Sb 3+ Doped scandium gallium garnet scintillator. Specifically, the oxide precursors are precisely mixed in stoichiometric ratios and sintered at high temperatures (1400-1600°C). During this process, the crystal structure of the material gradually takes shape, and by controlling the sintering time and temperature, the doping ions are uniformly incorporated into the scandium gallium garnet lattice.

[0008] The following are the innovative features of the present invention: During the crystal growth process, the A-site ions (such as Lu 3+ , Gd 3+ or Y 3+ ) selection and Cr 3+ and Sb 3+ The doping optimizes the local electronic environment in the lattice and promotes the efficient transfer of excited state energy from the matrix to the luminescent center of the doped ions. Under the processes of pre-firing, high-temperature sintering, and re-firing, the distribution of doped ions in the crystal is more uniform, reducing the formation of non-radiative recombination centers, thereby improving the luminescence efficiency and stability of the scintillator. The scintillator exhibits a high photon yield in the near-infrared band and meets the actual needs of radiation detection.

[0009] The method comprises the following steps:

[0010] Step 1, the main raw materials required include: A-site ion source (yttrium oxide Y2O3, gadolinium oxide Gd2O3 or lutetium oxide Lu2O3), scandium oxide (Sc2O3), gallium oxide (Ga2O3) and chromium source (Cr2O3) and antimony source (Sb2O3) for doping. Each raw material is accurately weighed according to the stoichiometric ratio to ensure the accuracy of the chemical composition of the target scintillator. The weighed raw materials are placed in a ball mill, and an appropriate amount of ethanol (2-3 ml) is added for sufficient ball milling and mixing. The speed is maintained at 300 rpm during the ball milling process, and the time is 12-24 hours to ensure that the raw materials are evenly mixed.

[0011] Step 2: Dry the slurry after ball milling by vacuum drying to remove ethanol. Dry at 50-80°C for 8-10 hours. After drying, sieve the mixture through a 100-200 mesh standard sieve to further homogenize the particle size and ensure that the raw materials can react evenly during the subsequent sintering process. The powder after screening should have no obvious agglomeration.

[0012] Step 3: Place the sieved powder in a crucible for preliminary sintering (pre-sintering) to remove the volatile components that may remain in the precursor and complete the initial phase formation. The pre-sintering temperature is controlled at 800-900°C, the sintering time is 4-6 hours, and it is carried out in an air atmosphere.

[0013] Step 4: The sintered material is ground again and passed through a 200-mesh standard sieve. The fine powder material is then placed in a crucible for high-temperature sintering. This process is a key step in forming the target scintillator crystal structure. The temperature is usually 1400-1500°C. To avoid overburning of the material or crystal defects, the heating rate must be precisely controlled (3-5°C / min). The sintering time is 5-8 hours. Continue to keep the process in an air atmosphere. At this temperature, the material crystal is fully formed, making the Cr 3+ and Sb 3+ It is effectively incorporated into the scandium gallium garnet crystal lattice and then slowly cooled to room temperature in a furnace.

[0014] Step 5: The product after high-temperature sintering is subjected to re-sintering treatment. The purpose is to optimize the crystal structure by re-sintering, reduce the defects and stress inside the material, and further improve the scintillation performance of the material. The re-sintering temperature is slightly lower, generally 1000-1200℃, and the sintering time is 4-6 hours. This step can improve the mechanical strength of the material while ensuring that Cr 3+ and Sb 3+ Evenly distributed in the lattice, it promotes further optimization of the energy transfer pathway, thereby improving the near-infrared luminescence efficiency. After the re-sintering is completed, the sample needs to be slowly cooled to room temperature in the furnace.

[0015] Furthermore, in the step 1, the following proportions are weighed: the amount of A-site ion oxide material is 3 mmol (1.19 g Lu2O3, 1.09 g Gd2O3 or 0.68 g Y2O3), scandium oxide (Sc2O3) is 2-x mmol, specifically 0.138×(2-x) g, gallium oxide (Ga2O3) is 3 mmol, specifically 0.55 g, the chromium source (Cr2O3) and antimony source (Sb2O3) required for doping ions are x mol, specifically 0.152×xg and 0.291×xg, and the doping concentration is usually controlled at x=1-10%, and x=5% is the best performance.

[0016] Furthermore, the target scintillator is chromium and antimony doped scandium gallium garnet, which belongs to the cubic system and has high symmetry, and the space group is Its chemical formula can be expressed as A3Sc2Ga3O 12 :Cr 3+ and A3Sc2Ga3O 12 :Sb 3+ . Among them, the A-site cation is composed of lutetium (Lu), gadolinium (Gd) or yttrium (Y), and is located at the center of the 8-coordinated cube. The B-site cations scandium (Sc) and gallium (Ga) occupy the octahedral and tetrahedral positions of 6 and 4 coordination respectively, forming a complex three-dimensional network; oxygen (O) forms a stable oxygen octahedron in the crystal structure, connecting each metal cation to ensure the integrity and stability of the structure. This multiple coordination environment contributes to effective energy transfer and improved luminescence efficiency. Chromium ion (Cr 3+ ) and antimony ions (Sb 3+ ) doping can achieve efficient energy transfer and radiative recombination after being excited in a specific coordination environment, thereby generating near-infrared luminescence, significantly enhancing the application potential of the material in the field of radiation detection.

[0017] The chromium and antimony doped scandium gallium garnet scintillator of the present invention effectively solves the problem of uneven mixing of samples in the early stage. By adopting a continuous multi-stage sintering process, not only good growth of the target material is achieved, but also the distribution of doping ions is optimized. This treatment method significantly improves the crystallinity of the material, thereby enhancing the scintillation performance.

[0018] Compared with the prior art, the technical solution of the present invention has the following significant advantages:

[0019] 1. Uniform doping distribution:

[0020] Through improved mixing and sintering processes, the present invention ensures uniform distribution of doping ions in scandium gallium garnet, thereby maximizing luminous efficiency. In the prior art, uneven doping often leads to fluctuations in material properties, but the present invention effectively avoids this problem.

[0021] 2.Excellent crystallinity:

[0022] The continuous multi-stage sintering method significantly improves the crystallinity of the target material, which is crucial for improving the scintillation performance. Compared with the traditional single sintering method, the multi-stage sintering process of the present invention can better control the crystallization process and improve the overall performance of the material.

[0023] 3. Wide application potential:

[0024] The improved crystallinity and uniform doping distribution enable the scintillator of the present invention to exhibit excellent luminescence performance in the near-infrared band, which can meet the high-end application requirements in the fields of radiation detection, medical imaging, etc. At present, there are few reports on the realization of near-infrared scintillation luminescence in garnet structure crystals and their application in radiation detection, which further highlights the obvious competitive advantage of the present invention over the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Gd3Sc2Ga3O 12 :Cr 3+ XRD patterns simulated with the corresponding crystalline phases.

[0026] Figure 2 Gd3Sc2Ga3O 12 :Cr 3+ Fluorescence excitation spectrum and emission spectrum measured by spectrometer.

[0027] Figure 3 A3Sc2Ga3O 12 :Cr 3+ and A3Sc2Ga3O 12 :Sb 3+ Spectrum of (A=Lu,Gd,Y) under X-ray irradiation excitation.

[0028] Figure 4 Gd3Sc2Ga3O 12 :Cr 3+ Environmental stability test chart.

[0029] Figure 5 Gd3Sc2Ga3O 12 :Cr 3+ Stability test diagram under X-ray irradiation.

[0030] Figure 6 Gd3Sc2Ga3O 12 :Cr 3+ Linear response test diagram of dose rate and luminous intensity under X-ray irradiation. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with implementation examples, but the present invention is not limited to the scope of these implementation examples.

[0032] Example:

[0033] A3Sc2Ga3O 12 :Cr 3+ and A3Sc2Ga3O 12 :Sb 3+Preparation of (A=Lu, Gd, Y) near-infrared scintillator: According to the target chemical composition, select appropriate precursor materials and weigh them according to the following proportions: the amount of A-site ion (Lu2O3, Gd2O3 or Y2O3) oxide material is 3mmol, the amount of scandium oxide (Sc2O3) is 2-x mmol, the amount of gallium oxide (Ga2O3) material is 3mmol, the chromium source (Cr2O3) and antimony source (Sb2O3) required for doping ions are x mmol, and the doping concentration is usually controlled at x=1-10%, and x=5% is the best performance.

[0034] Add the above-mentioned precursor materials weighed in a stoichiometric ratio to a ball mill, add 3 ml of ethanol, and then place the ball mill in a ball mill for 12-24 hours. Keep the rotation speed at 300 rpm during the ball milling process to ensure that the precursor materials are fully mixed to form a uniform mixture. After the ball milling is completed, take the slurry out of the ball mill, place it in a vacuum drying oven, dry it at 50-80 ° C for 8-10 hours, remove the solvent, and obtain a dried mixed powder. Sieve the dried mixed powder through a 100-200 mesh standard sieve to ensure that the powder particles are fine, uniform and free of agglomeration. The sieved powder is set aside for the next sintering process.

[0035] The sieved mixed powder is placed in an alumina crucible and placed in a high-temperature furnace for initial sintering. The initial sintering temperature is set to 900°C and the constant temperature time is maintained for 6 hours to promote the solid-phase reaction between the precursors to fully proceed and initially generate the scandium gallium garnet crystal structure. The material after initial sintering is ground again and passed through a 200-mesh standard sieve to ensure that the powder particle size is uniform. Then the powder is put back into the crucible and placed in a high-temperature sintering furnace for high-temperature sintering. The high-temperature sintering temperature is set to 1400°C and the heating rate is 3°C / min. Maintain a constant temperature for 8 hours to ensure that the scandium gallium garnet crystals are fully formed and the doped ions are evenly distributed in the lattice. After sintering, the furnace is cooled to room temperature to obtain a high-temperature sintered sample. The material at this time should be a high-density, well-crystalline chromium and antimony doped scandium gallium garnet scintillator.

[0036] In order to further optimize the scintillation performance of the material, especially to improve the crystallinity of the material and reduce lattice defects, the material after high-temperature sintering can be subjected to re-sintering treatment. The sample after high-temperature sintering is placed in a furnace, and the re-sintering temperature is set to 1200°C for 4 hours. During the re-sintering process, the tiny defects in the crystal can be repaired, and the uniform distribution of the luminescence center is promoted. After the re-sintering is completed, the furnace is slowly cooled to room temperature to obtain the optimized scintillator material. The re-sintered material is ground into powder and can be used for subsequent phase (XRD), photoluminescence (PL), scintillation performance tests and other characterization tests.

[0037] Gd3Sc2Ga3O12 :Cr 3+ As a typical example, its XRD results are as follows Figure 1 As shown in the figure, the experimental results match the simulation results well, and no impurity phase is produced. It can be inferred that we have successfully synthesized a chromium-doped scandium gallium garnet near-infrared scintillator with a relatively pure phase. Fluorescence spectrum test shows that the product has three excitation peaks (273nm, 416nm, 564nm), which are attributed to Cr 3+ of 4 A2→ 4 T1( 4 P), 4 A2→ 4 T1( 4 F), 4 A2→ 4 T2( 4 F) transition; the emission peak is at 720nm, attributed to Cr 3+ Spin allowed 4 T2→ 4 A2 transition, bright red-near infrared luminescence ( Figure 2 ). There is no obvious overlap between the excitation and emission peaks, indicating that there is no obvious self-absorption phenomenon in this material.

[0038] Figure 3 A3Sc2Ga3O 12 :Cr 3+ and A3Sc2Ga3O 12 :Sb 3+ (A=Lu,Gd,Y) Spectrum under X-ray irradiation excitation. Under 50KV, 200uA X-ray excitation, the samples all show bright near-infrared emission. At the same time, by comparing with traditional commercial scintillators LYSO:Ce and BGO, the calculation results show that A3Sc2Ga3O 12 :Cr 3+ (A=Lu, Gd, Y) have high photon yields of about 40000, 40000, 45000 photons / MeV respectively; A3Sc2Ga3O 12 :Sb 3+ (A=Lu, Gd, Y) have high photon yields of about 7000, 8500, 8000 photons / MeV respectively

[0039] Gd3Sc2Ga3O 12 :Cr 3+ For example, through the XRD spectrum results, it can be observed that the diffraction peak position of the newly synthesized product matches that of the product after being placed in the air for three months, proving that it has high environmental stability ( Figure 4At the same time, the sample still maintained 96% of its luminescence intensity after 80 minutes of X-ray irradiation, which also proved its high X-ray irradiation stability ( Figure 5 ). In addition, Gd3Sc2Ga3O 12 :Cr 3+ It also shows a linear response between high irradiation dose rate and luminous intensity ( Figure 6 ).

[0040] In summary, the above results indicate that Cr and Sb doped ScGaG near-infrared scintillators have excellent scintillation properties and potential commercial application value.

Claims

1. A garnet structure near-infrared luminescent scintillator, characterized in that: The target scintillator is chromium and antimony doped scandium gallium garnet, which belongs to the cubic system and has high symmetry. The space group is Its chemical formula is A3Sc2Ga3O 12 :Cr 3+ and A3Sc2Ga3O 12 :Sb 3+ ; Among them, the A-site cation is composed of lutetium Lu, gadolinium Gd or yttrium Y, located at the center of the 8-coordinated cube; the B-site cations scandium Sc and gallium Ga occupy the octahedral and tetrahedral positions of 6 and 4 coordination respectively, forming a complex three-dimensional network; oxygen O forms a stable oxygen octahedron in the crystal structure, connecting each metal cation, thereby ensuring the integrity and stability of the structure, and the multiple coordination environment is conducive to effective energy transfer and improvement of luminescence efficiency; chromium ion Cr 3+ and antimony ions Sb 3+ After being excited in a specific coordination environment, the doping can achieve energy transfer and radiative recombination, thereby producing near-infrared luminescence, significantly enhancing the application potential of the material in the field of radiation detection.

2. A method for preparing the garnet structure near-infrared luminescent scintillator as claimed in claim 1, characterized in that: The method comprises the following steps: Step 1, the required raw materials include: A-site ion source, scandium oxide Sc2O3, gallium oxide Ga2O3, and chromium source Cr2O3 and antimony source Sb2O3 for doping; the A-site ion includes yttrium oxide Y2O3, gadolinium oxide Gd2O3 or lutetium oxide Lu2O3; Accurately weigh each raw material according to the stoichiometric ratio to ensure the accuracy of the chemical composition of the target scintillator; place the weighed raw materials in a ball mill, add 2-3 ml of ethanol for thorough ball milling and mixing, and keep the speed at 300 rpm during the ball milling process for 12-24 hours to ensure that the raw materials are evenly mixed; Step 2, the slurry after ball milling is dried by vacuum drying to remove ethanol; dried at 50-80°C for 8-10 hours, and after drying, the mixture is sieved through a 100-200 mesh standard sieve to further homogenize the particle size to ensure that the raw materials can react evenly during the subsequent sintering process; the powder after screening should have no obvious agglomeration phenomenon; Step 3, placing the sieved powder in a crucible for preliminary sintering to remove the volatile components that may remain in the precursor and complete the preliminary phase formation; the pre-sintering temperature is controlled at 800-900° C., the sintering time is 4-6 hours, and it is carried out in an air atmosphere; Step 4, the material after the initial sintering is ground again and passed through a 200-mesh standard sieve, and then the fine powder material is placed in a crucible for high-temperature sintering; this process is a key step in forming the target scintillator crystal structure, the temperature is 1400-1500°C, in order to avoid overburning of the material or crystal defects, the heating rate needs to be precisely controlled: 3-5°C / min; the sintering time is 5-8 hours; continue to be carried out in an air atmosphere; at this temperature, the material crystal is fully formed, so that the doping ions are effectively incorporated into the lattice of the scandium gallium garnet; then slowly cooled to room temperature in the furnace; Step 5, the product after high-temperature sintering is subjected to re-sintering treatment. By re-sintering, the crystal structure is optimized, the defects and stress inside the material are reduced, and the scintillation performance of the material is improved; the re-sintering temperature is as low as 1000-1200°C, and the sintering time is 4-6 hours; it can improve the mechanical strength of the material, while ensuring that the doped ions are evenly distributed in the lattice, promoting the optimization of the energy transfer pathway, and improving the near-infrared luminescence efficiency; after the re-sintering is completed, the sample needs to be slowly cooled to room temperature in the furnace.

3. The method for preparing a garnet structure near-infrared luminescent scintillator according to claim 2, characterized in that: In the step 1, the following proportions are weighed: the amount of the A-site ion oxide material is 3 mmol, 1.19 g Lu2O3, 1.09 g Gd2O3 or 0.68 g Y2O3, the scandium oxide Sc2O3 is 2-x mmol, specifically 0.138×(2-x) g, the gallium oxide Ga2O3 is 3 mmol, specifically 0.55 g, the chromium source Cr2O3 and the antimony source Sb2O3 required for doping ions are x mol, specifically 0.152×xg and 0.291×xg, and the doping concentration is usually controlled at x=1-10%, and x=5% is the best performance.

Citation Information

Cited By

  • Chromium ion doped near-infrared scintillation crystal and preparation method and application thereof

    CN120889031A